DIGITAL COGNITIVE-BEHAVIORAL THERAPY FOR INSOMNIA (dCBT-I) AS A METHOD OF HYPNOTIC MEDICATION REDUCTION USE - Zofia Hałabuda; Kornelia Rynkiewicz (International Journal of Innovative Technologies in Social Science, 2026)
Introduction & objective: Insomnia, being an established health problem, has led to the development of various ways of treatment. While Cognitive Behavioral Therapy is a gold standard of insomnia treatment, due to cost and accessibility limitations, pharmacological methods remain widely used. The most commonly used drugs are benzodiazepines and Z-drugs, which, due to their adverse effects and high dependency risk, impose various dangers. One of the “side effects” of insomnia treatment is the development of drug dependence. Well-established methods of combating these issues concern only benzodiazepines, Z-drug medication use reduction protocols are still unavailable. However, considering both these drugs, a slow dose reduction method is believed to be the most effective and safe. The newest research examines the use of digital CBT as a tool for reducing drug dependence. The results are promising, as combining slow dose reduction with digital CBT yields better outcomes than the previous approach. However, there is still limited data on the use of digital CBT in reducing reliance on pharmacological interventions in high-risk patient groups or among patients with high levels of dependency, the development of official protocols is needed. This literature review aims to assess progress in this field of medicine. Review methods: This review is based on a non-systematic review of PubMed articles published between 2008 and 2026. Brief description of state knowledge: In numerous studies, the efficacy of digital CBT is a safe and effective method of insomnia treatment. Concerning previous addiction reduction methods, the only established guidelines are those concerning benzodiazepine dependency, and they involve the method of slow dose reduction. Recent clinical trials suggest that combining digital CBT with dose reduction may be an alternative, demonstrating greater efficacy in treating pharmacological dependence.Summary: Digital CBT-I is not only an alternative to traditional face-to-face CBT for the management of insomnia but may also represent a scalable and clinically relevant strategy for reducing benzodiazepine and Z-drug dependence. Emerging evidence suggests that combining gradual dose reduction with digital CBT-I may enhance deprescribing outcomes compared with tapering alone. However, limited real‑world safety data highlight the need for further research to define better safety and protocols for dependency reduction in patients overusing benzodiazepines and Z-drugs using digital CBT.